Ouro Preto: paisagem em transformação - Marina Salgado (2010)
The main focus of this research is to investigate both the development of new urban structures caused by the rapid expansion of cities as well as traditional structures of the historic city of Ouro Preto, located in the state of Minas Gerais, Brazil, through the application of methodologies developed by Urban Morphology schools. The dilemma between tradition and modernity is a recurrent theme, especially in the colonial towns of Minas Gerais. These towns contain a historic core that must be preserved, thus proposed expansions must be concerned with maintaining the quality of the citys historic centre landscape: its buildings, its urban fabric, and its morphotypological characteristics. Over the years, the landscape quality of Ouro Pretos historic centre has not been respected nor even taken into consideration as a basis for future interventions or the drafting of urban plans. The lack of dialogue among the various urban structures leads to a loss of the citys historical character as a whole. Due to the dynamic characteristic of the urban landscape, the city development and renewal can not be stopped. However, growth of the urban environment must guided in a balanced manner so that the economic interests of some social classes do not outweigh community interests. Through this study, we hope to contribute to research on the topic of urban morphology, as well as to the quality of the landscape, since research on this subject can aid in the decision-making process regarding the conservation of historic urban centres.